2020
DOI: 10.1021/acs.jmedchem.9b02151
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of an EPAC1-Selective Competitive Partial Agonist

Abstract: The exchange protein activated by cAMP (EPAC) is a promising drug target for a wide disease range, from neurodegeneration and infections to cancer and cardiovascular conditions. A novel partial agonist of the EPAC isoform 1 (EPAC1), I942, was recently discovered, but its mechanism of action remains poorly understood. Here, we utilize NMR spectroscopy to map the I942–EPAC1 interactions at atomic resolution and propose a mechanism for I942 partial agonism. We found that I942 interacts with the phosphate binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 81 publications
(230 reference statements)
0
33
0
Order By: Relevance
“…Measurements of cNMP-binding affinities for HCN4 were achieved via competitive binding with the fluorescent cAMP analog, 8-NBD-cAMP, using an approach similar to the protocols described previously (49)(50)(51). The K d of 8-NBD-cAMP for each HCN4 construct was initially determined via a titration in which the 8-NBD-cAMP concentration was fixed at 500 nM and the HCN4 construct was added at concentrations ranging from 0.1 to 50 mM.…”
Section: Affinity Measurementsmentioning
confidence: 99%
“…Measurements of cNMP-binding affinities for HCN4 were achieved via competitive binding with the fluorescent cAMP analog, 8-NBD-cAMP, using an approach similar to the protocols described previously (49)(50)(51). The K d of 8-NBD-cAMP for each HCN4 construct was initially determined via a titration in which the 8-NBD-cAMP concentration was fixed at 500 nM and the HCN4 construct was added at concentrations ranging from 0.1 to 50 mM.…”
Section: Affinity Measurementsmentioning
confidence: 99%
“…Interestingly, depletion of ANXA2 in ECs reduced the enhanced binding force between reOmpB and ECs in the presence of I942 (versus the WT group, p = 0.09), independent of its concentration in the culture medium (Figure S2). Taking advantage of a recently developed non-cAMP analogue, an EPAC1 specific activator named I942 that competitively binds the cyclic nucleotide-binding domain of EPAC1 [50][51][52], we observed that I942 at 5 µM in culture media enhanced the interacting force between reOmpB and a live WT BMEC (p < 0.05) (Figure 4). Depletion of ANXA2 in ECs diminished reOmpB binding forces to the ANXA2-KO BMEC surface (p < 0.01) (Figure 4), corroborating our previous report that anti-ANXA2 antibody weakens the interacting force between reOmpB and a living EC [44].…”
Section: Rickettsial Ompb Shows a Host Epac1-dependent Binding Strength On The Surface Of A Living Ecmentioning
confidence: 98%
“…Recently, Yarwood’s group identified, in a high throughput screening (HTS) study, the first known non-cyclic nucleotide (NCN) EPAC1 agonist, I942 with in vitro application [ 32 , 33 ]. NMR spectrometry analysis demonstrated that I942 can stabilize an inhibition-incompetent activation intermediate state of EPAC1 distinct from both active and inactive states [ 34 ]. Additionally, in a study carried out by the Zhou’s group, a series of non-cyclic nucleotide activators named 25g, 25q, 25n, 25u, 25e, and 25f with good selectivity over PKA were identified.…”
Section: Epac1 Pharmacological Modulatorsmentioning
confidence: 99%